Electrochemical Sensors and Biosensors for the Analysis of Tea Components: A Bibliometric Review - Shao, Jinhua; Wang, Chao; Shen, Yiling; Shi, Jinlei; Ding, Dongqing (Frontiers in Chemistry, 2022)
Tea is a very popular beverage worldwide. Due to the concern about the nutritional value and safety of tea consumption, a lot of research has been devoted to the analysis of tea composition, quality monitoring and tea identification. Among them, investigation of tea using electrochemical biosensing technology has attracted considerable attention in the last two decades. Although electrochemical biosensing has not yet become the most commonly used technique for tea analysis, it has become a very promising technology due to its high sensitivity, rapidity and low cost. In this review, we provide a systematic survey of the literature on electrochemical analysis of tea from 1994-2021 through bibliometric analysis. The bibliometric analysis revealed that electrochemical analysis can be divided into three distinct stages in the study of tea. First, electrochemical techniques were employed only as a detection method after chromatographic separation of samples. Since many important components in tea have electrochemical activity, such as tea polyphenols, gallic acid, caffeic acid, etc., their electrochemical behavior began to be studied. With the rapid development of materials science, especially nanomaterials, high-performance electrochemical sensors have gradually become a hot research topic. This review not only summarizes these steps, but also compares the important literature among them. Based on the bibliometric evidence, this review also suggests future perspectives in this area.